Experimental Study on Design of External Shading Devices in Dental Unit Room - Rahmaniya, Liya Isma; Dwiyanto, Agung (Department of Architecture, Faculty of Engineering, Universitas Diponegoro, Indonesia., 2024)
Experimental study using software simulation is frequently employed as a tool to minimize errors in design and predict design decisions. In addition to considering the functions of the building and other requirements, architects are required to understand the context and possess the ability to optimize the climatic potential of the construction site. Solar gain is a crucial factor, as insufficient sunlight entering a space can result in inadequate illumination, while excessive sunlight can increase the building's heat gain. Therefore, the key to success in design lies in optimizing lighting and heat gain proportionally to address these challenges. This research utilizes an experimental method by identifying the location, orientation, material, and function of the space. The objective of this study is to find an optimal external shading device for shading the Dental Unit area in the Central Laboratory building at the Diponegoro University. The results of the research indicate that the use of 3 types shading devices can reduce the average sunlight gain by 10-15%, offering significant potential for lowering energy consumption in the Central Laboratory building of the Faculty of Medicine at Diponegoro University in Semarang, Indonesia.